2018
DOI: 10.1159/000494664
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Assisted Peritoneal Dialysis Modality on Outcomes: A Cohort Study of the French Language Peritoneal Dialysis Registry

Abstract: Background: Patients on peritoneal dialysis (PD) can be assisted by a nurse or a family member and treated either by automated PD (APD) or continuous ambulatory PD (CAPD). The aim of this study was to evaluate the effect of PD modality and type of assistance on the risk of transfer to haemodialysis (HD) and on the peritonitis risk in assisted PD patients. Method: This was a retrospective study based on data from the French Language PD Registry. All adults starting assisted PD in France between 2006 and 2015 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 43 publications
0
25
1
Order By: Relevance
“…The prevalence of patients with end‐stage kidney disease (ESKD) in need of chronic life‐sustaining renal replacement therapy increases substantially among older age groups (United States Renal Data System 2018). As peritoneal dialysis (PD) confers advantages for older individuals, including home‐based treatment, avoiding the need to travel to and from the dialysis unit, and fewer haemodynamic variations (Guilloteau et al 2018), the number of older adults undergoing PD is increasing, especially in developing countries. In 2016, it was reported that over 33% of patients undergoing PD in China were above the age of 60 (Wu et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of patients with end‐stage kidney disease (ESKD) in need of chronic life‐sustaining renal replacement therapy increases substantially among older age groups (United States Renal Data System 2018). As peritoneal dialysis (PD) confers advantages for older individuals, including home‐based treatment, avoiding the need to travel to and from the dialysis unit, and fewer haemodynamic variations (Guilloteau et al 2018), the number of older adults undergoing PD is increasing, especially in developing countries. In 2016, it was reported that over 33% of patients undergoing PD in China were above the age of 60 (Wu et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective observational study in the United Kingdom 9 showed that the peritonitis rate was 1:36.7 patient-months for APD-treated patients and 1:28.8 patient-months for CAPD-treated patients, representing an odds ratio of 0.78 favoring APD. Conversely, three recent observational studies found that PD modality was unassociated with a higher likelihood of developing peritonitis 11 13 . Differing study populations, follow-up times, improvements in CAPD and APD connection systems, and advances in nursing care and dialysis treatment may have led to the differing results in these studies.…”
Section: Discussionmentioning
confidence: 91%
“…Peritonitis is a major cause of PD failure via structural and functional alterations of the peritoneal membrane 16 , which can lead to life-threatening events 9 , 17 . Previous reports have shown a relationship between PD modality and peritonitis, but these studies are observational 9 13 rather than randomized control trials 14 , 15 . Results of many studies have shown that patients on APD have a lower or similar incidence of peritonitis than do those on CAPD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 2 was depicted to demonstrate how patients' treatment adherence has changed after switching to RM-APD. According to Figure 2, alarms received from the device decreased within months, and treatment adherence of patients increased (from 4 [3][4][5][6][7][8] to 2 [0-3], p = 0.001). Also, patient median body weight decreased from 62.7 to 61 kg within 6 months.…”
Section: Resultsmentioning
confidence: 99%